2019
DOI: 10.1109/jiot.2019.2905952
|View full text |Cite
|
Sign up to set email alerts
|

An Energy Efficient Hybrid MAC Protocol With Dynamic Sleep-Based Scheduling for High Density IoT Networks

Abstract: Advances in the development of low powered sensors has meant they can now provide solutions to IoT networks that suffer from restricted power supply and a lack of resource facilities. In this paper, a hybrid TDMA-CSMA/CA MAC protocol has been proposed that efficiently utilises the energy of the nodes and dynamically adapts the sleep/wake-up periods according to the variance in the network loads. This hybrid protocol first schedules the TDMA time slots (T DM A slots), and then allocates each slot to a group of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(24 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…Cross-layer scheduling structures have been developed between three layers: regulation of the source rate at the transport layer, optimizing multipath routing and flowrate at the network layer, and optimizing the MAC layer's duty cycle. In [83], a hybrid time division multiple access (TDMA) based medium access protocol has been suggested that avoids collisions and effectively uses the energy of the nodes and dynamically schedules the sleep/wake-up modes according to variability at the nodes. This increase the energy conservation by 40-60% compared to the IEEE 802.15.4-based MAC protocol.…”
Section: Offline and Online Energy Scheduling And Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross-layer scheduling structures have been developed between three layers: regulation of the source rate at the transport layer, optimizing multipath routing and flowrate at the network layer, and optimizing the MAC layer's duty cycle. In [83], a hybrid time division multiple access (TDMA) based medium access protocol has been suggested that avoids collisions and effectively uses the energy of the nodes and dynamically schedules the sleep/wake-up modes according to variability at the nodes. This increase the energy conservation by 40-60% compared to the IEEE 802.15.4-based MAC protocol.…”
Section: Offline and Online Energy Scheduling And Optimizationmentioning
confidence: 99%
“…In [81], the authors presented information-theoretic limits and scheduling policies, and medium access control (MAC) protocols are presented in [82], [83]. In addition to it, the authors discuss simultaneous information and power transfer.…”
Section: Introductionmentioning
confidence: 99%
“…BirdMAC offers better energy-saving capabilities with infrequent synchronization of nodes’ clocks. A time-division multiple access (TDMA) and carrier-sense multiple access with collision avoidance (CSMA/CA)-based hybrid MAC protocol targeted for highly dense IoT networks was presented in [ 38 ]. It utilizes the energy of the nodes and dynamically adapts the sleep/wake-up period according to the variance in the network loads.…”
Section: Preliminariesmentioning
confidence: 99%
“…Here we review various duty cycle aware protocols, which make sure that the sleep phases are given most of the cycle, while the awake phases are turned ON when needed [7]. This reduces the power consumption by many folds [8], and reduces latency in the network. Authors in [9] evaluate that the energy consumption is more in wake phase than sleep phase.…”
Section: Literature Surveymentioning
confidence: 99%